The Effect of Teacher Professional Development on Implementing Engineering in Elementary Schools - Malone, Kathy L.; Porter, Teresa; West, Meg E.; Kajfez, Rachel L.; Irving, Karen E. (Purdue University Press, 2019)
Increased attention on the implementation of engineering education into elementary school classrooms aims to start preparing students early for potential engineering careers. In order to efficiently and effectively add engineering concepts to the curriculum, appropriate development and facilitation of engineering design challenges are required. Therefore, professional development programs are necessary to educate teachers about engineering and how to adequately teach it. This paper explores the effects of an engineering professional development program for practicing teachers. The program included training elementary teachers about how to implement units from Engineering is Elementary (EiE) by the Science Museum of Boston into their classes. Semi-structured focus group interviews were conducted, both prior to and following the implementation of the EiE units over an academic year. The interviews were transcribed and coded using open-coding, resulting in the development of a codebook. The codes were further analyzed until salient themes emerged that can be used to improve the training and better understand how teachers integrate engineering into their classrooms. The results show that many teachers need training to learn about engineering practices, as well as pedagogical guidance on how to incorporate engineering concepts into their lessons. However, not surprisingly, limited resources such as time, money, materials, and knowledge restrict efficient curricula implementation. We believe these findings reemphasize the need for science, technology, engineering, and mathematics professional development programs to educate K–12 teachers about engineering and will be useful to others interested in integrating engineering into K–12 curricula.